2019
DOI: 10.1161/strokeaha.118.023353
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Stroke, but Not Coronary Heart Disease, in Elderly Patients With Sleep Apnea

Abstract: Background and Purpose— The influence of age on the relationship between obstructive sleep apnea (OSA) and the incidence of hard cardiovascular events remains controversial. We sought to analyze the relationship between OSA and the incidence of stroke and coronary heart disease in a large cohort of elderly patients, as well as to investigate the role of continuous positive airway pressure (CPAP) treatment in these associations. Methods— Post hoc analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 11 publications
2
35
0
1
Order By: Relevance
“…Primary studies: Four studies of class 3 or 4 quality were included. Two studies assessed CPAP [73,74]. Two studies assessed the effect of uvulopalatopharyngoplasty (UPPP) [75] or tracheostomy [76].…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary studies: Four studies of class 3 or 4 quality were included. Two studies assessed CPAP [73,74]. Two studies assessed the effect of uvulopalatopharyngoplasty (UPPP) [75] or tracheostomy [76].…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…CATALAN-SERRA et al [73] examined the incidence of stroke in OSA patients with CPAP treatment in a prospective, observational cohort from Spain. In the 6-year median follow-up, OSA with AHI ⩾30 events per h and CPAP not prescribed or compliance <4 h per day had significantly higher cumulative incidence of stroke compared with the reference group of individuals with AHI <15 events per h (log-rank test, 11.87, p=0.001; HR 3.42, 95% CI 1.37-8.52) after adjustments for age, body mass index, hypertension, sex, smoking habit, Epworth Sleepiness Scale and atrial fibrillation (table e5).…”
Section: Overview Of the Evidencementioning
confidence: 99%
“…OSA, the most frequently reported SDB pattern in the context of stroke, and central sleep apnoea (CSA) including Cheyne-Stokes respiration (CSR) are both observed more frequently in patients with incident stroke compared to the general population [10,12,[17][18][19][20][21][22][23][24][25][26][27][28][29]. Accumulating evidence suggest the existence of a bidirectional association between SDB and cerebrovascular diseases; on the one hand, SDB is a severity-dependent risk factor for stroke and for stroke-related unfavourable short-term and long-term outcomes and on the other hand, stroke itself is a cause of new onset SDB or an aggravating factor of pre-existing SDB [6,30,34].…”
Section: Introductionmentioning
confidence: 99%
“…Our finding of a potential harmful association of long sleep duration and stroke but not cardiac events in OSA patients contrasts with studies of the general population. 14,15 This may reflect the underlying mechanism of CV diseases and OSA, where a study has shown untreated severe OSA to be an independent risk factor for stroke but not coronary heart disease in elderly patients, 16 and two meta-analyses reporting much stronger associations of OSA and stroke rather than cardiac events. 17,18 One explanation is an apparent differential link in that acute or long-term intermittent hypoxia may impact differently on the brain compared to the heart in relation to variable collateral vasculature.…”
Section: Discussionmentioning
confidence: 99%